Derivación de valores económicos de la producción de leche de bovinos en la parroquia Eloy Alfaro utilizando funciones de beneficio. - Iza Chicaiza, Diego Armando (2022)
The dairy production line is distinguished as a set of factors that interact in an economic action, this production chain begins in the primary sector (producers) to the final consumer; and whose particularity of each link directly alters the efficiency and obtaining of dairy production as a whole. The present work was carried out in the province of Cotopaxi, canton Latacunga, parish Eloy Alfaro, at an altitude of 2850 meters above sea level, with a temperature of 13°C and a cold temperate climate. Therefore, the objective of the research was to derive the economic values of bovine milk production in the Eloy Alfaro parish using profit functions. In order to know the existing situation of the parish, meetings were arranged with the inhabitants of the Tilipulo, La Calera and Taniloma neighborhoods, to collect information through surveys directed to the producers, establishing the valuation of each of the animals present in each farm. The results indicate that, in the Eloy Alfaro parish, the production system in its totality is carried out with the traditional herds, the predominant type of breed is the Holstein Friesian (98%) and the rest are mestizos, Brown Swiss or Jersey; the average daily milk production was 5 kg per day, with a density of 1,027 kg/ml. Economically, it has been shown that most of the farms have a higher expenditure in the cattle feeding, while on the other hand the payment per liter of milk is 0.38 cents. Consequently, based on the production costs and the profitability of each producer, the genetic selection criteria determined were the daily weight gain (GDP) for the necessary efficiency in feeding, fertility for low pregnancy rates, days open (175) and finally milk production for the parameters established by the dairy industry for a greater economic return, these criteria will allow improving productivity rates within each farm as long as management parameters such as records, feeding and sanitation are guaranteed.